Right anterior thoracotomy vs. upper hemisternotomy for aortic valve replacement with Perceval S: is there a difference? - Okiljevic, Bogdan; Raickovic, Tatjana; Zivkovic, Igor; Vukovic, Petar; Milicic, Miroslav; Stojanovic, Ivan; Milacic, Petar; Micovic, Slobodan (Frontiers in Cardiovascular Medicine, 2024)
BackgroundOur study aimed to evaluate the early outcomes of aortic valve replacement with Perceval S sutureless valve through the right anterior thoracotomy and upper hemisternotomy approaches, and to determine if there are any differences between these two approaches.MethodsWe carried out a study using data from 174 patients who underwent minimally invasive Perceval S valve implantation for aortic valve stenosis between January 2018 and August 2023. This was a retrospective, single-center observational study. The patients were divided into two groups: the hemisternotomy group (n = 100) and the right anterior thoracotomy group (n = 74).ResultsThe overall in-hospital mortality was 1,7%. The cardiopulmonary bypass and cross-clamp times were longer in the right anterior thoracotomy group (p < .001). There were no statistically significant differences in terms of stroke, paravalvular leak, mechanical ventilation time, blood transfusion requirements, pacemaker implantation, reexploration for bleeding, conversion, wound infection, or in-hospital stay. Postoperative chest drainage was lower (p < .001) and postoperative atrial fibrillation occurred less frequently (p = .044) in the right anterior thoracotomy group. The median intensive care unit stay was shorter in the right anterior thoracotomy group (p = .018).ConclusionAortic valve replacement with the Perceval S valve through either an upper hemisternotomy or a right anterior thoracotomy is a procedure associated with low perioperative complication rates. Right anterior thoracotomy for an aortic valve replacement with the Perceval S valve was associated with lower postoperative bleeding, a lower postoperative atrial fibrillation incidence and a shorter intensive care unit stay compared to upper hemistornotomy.